Pengembangan Media Pembelajaran Sejarah Indonesia Berbasis Android Mengunakan Algoritma Fisher Yates - Muntahanah Muntahanah; Ahmad Novianto; Ardi Wijaya; Yovi Apridiansyah (Jurnal Media Infotama, 2022)
This study was an application development from former research that makes an android-based Indonesian history learning media application. From previous studies, the researcher did not employ randomization or algorithms. Meanwhile, in this study, it was developed using the Fisher-Yates algorithm. This study utilized the UCD method which conducted interviews with users or research sites so that they could get results on the needs, designs, and feasibility as well as tests on applications or learning media. From the results of the research that has been conducted, it is found that this learning media can aid the learning system for students of State Junior High School 38. As a necessity and feasibility, this learning media is calculated using a Likert Scale and gets 81.2% results which are included in the statement strongly agree.